What Motivates People to Earn a Certification in Supply Chain Management? - Silvester Adi Surya Herjuna; Anak Agung Ngurah Perwira Redi (Enrichment : Journal of Management, 2022)
This research examines why people enter certification programs. This research examines the supply chain management certification program, the most popular in industry (McCaffery, Backus, & Maxwell, 2020). Extrinsic motivation (Lloyd & Mertens, 2018; Baumann & Bonner, 2016); intrinsic motivation (Quinn et al., 2021; Achtziger & Gollwitzer, 2018; Australian HR Institution, 2017); obtaining a reward or incentive (Australian HR Institution, 2017); and the cost is less than the master's program (Amoruso, 2020; Craig, 2020). AHP is used to rank the 4 criteria's primary aspects. The study sampled experts. Experts are someone with expertise and experience in a subject, system, or sector (Sharma, 2017; Skjong & Wentworth, 2001). This research indicated that incentives were the largest influence in joining a certification program. Extrinsic motivation is second, intrinsic motivation is third, and cost is fourth.